ANALISIS UMUR EKONOMIS ANGKUTAN KOTA STUDI KASUS: TRAYEK MARGAHAYU RAYA -LEDENG KOTAMADYA BANDUNG - Husniah, Hennie
Abstract : The thesis is concerned with the investigation of the economic life of a specific public transport (angkutan kota or angkot), both theoretically and practically. Theoretically, the economic life of the public transport is studied using mathematical models within various categories, namely, discrete model, continuous model, deterministic model and stochastic model. A new approach of a continuous stochastic model is explored as a modification of a continuous deterministic model previously developed by Bethuyne. Practically, the computation of the economic life of the public transport for certain trajectory in Bandung, that is the angkot serving the route of Margahayu Raya -- Ledeng, is discussed in this thesis. Several conclusions are found, among them is that the economic life of the angkot is affected by the level of the interest rate and the utility rate used in the computation. Further, it can also be concluded that the increase of the level of the interest rate increases the computed economic life of the angkot while the increase of the utility rate decreases the computed economic life of the angkot.